Global Disparities of Hypertension Prevalence and Control: A Systematic Analysis of Population-Based Studies From 90 Countries. Issue 6 (9th August 2016) - Mills, Katherine T.; Bundy, Joshua D.; Kelly, Tanika N.; Reed, Jennifer E.; Kearney, Patricia M.; Reynolds, Kristi; Chen, Jing; He, Jiang
Abstract : Background: Hypertension is the leading preventable cause of premature death worldwide. We examined global disparities of hypertension prevalence, awareness, treatment, and control in 2010 and compared secular changes from 2000 to 2010. Methods: We searched MEDLINE from 1995 through 2014 and supplemented with manual searches of retrieved article references. We included 135 population-based studies of 968 419 adults from 90 countries. Sex- and age-specific hypertension prevalences from each country were applied to population data to calculate regional and global numbers of hypertensive adults. Proportions of awareness, treatment, and control from each country were applied to hypertensive populations to obtain regional and global estimates. Results: In 2010, 31.1% (95% confidence interval, 30.0%–32.2%) of the world's adults had hypertension; 28.5% (27.3%–29.7%) in high-income countries and 31.5% (30.2%–32.9%) in low- and middle-income countries. An estimated 1.39 (1.34–1.44) billion people had hypertension in 2010: 349 (337–361) million in high-income countries and 1.04 (0.99–1.09) billion in low- and middle-income countries. From 2000 to 2010, the age-standardized prevalence of hypertension decreased by 2.6% in high-income countries, but increased by 7.7% in low- and middle-income countries. During the same period, the proportions of awareness (58.2% versus 67.0%), treatment (44.5% versus 55.6%), and control (17.9% versus 28.4%) increased substantially in high-income countries, whereas awareness (32.3% versus 37.9%) and treatment (24.9% versus 29.0%) increased less, and control (8.4% versus 7.7%) even slightly decreased in low- and middle-income countries. Conclusions: Global hypertension disparities are large and increasing. Collaborative efforts are urgently needed to combat the emerging hypertension burden in low- and middle-income countries. Abstract : Supplemental Digital Content is available in the text.